Sistem Informasi Penyebaran Lokasi Pelatihan Desa Berbasis GIS di Balai Besar Pengembangan Latihan Masyarakat Jakarta - Anhar Hawari; Agung Triayudi; Ira Diana Sholihati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Jakarta Large Community Development Training Center is one of the work units in the Ministry of Villages, Disadvantaged Regions Development and Transmigration, that has the task and function to train rural communities. Every year the community trained can reach thousands of people consisting of several villages. Because the development of information technology maps can be displayed digitally by using Geographic Information Systems (GIS), so that it is more efficient and easily accessed by anyone and anywhere, this digital map will be integrated using the web. This research will be developed using HTML, CSS and Javascript website frameworks as front end, PHP as backend and MySQL by utilizing phpMyAdmin features as a database, all the programming languages will be processed using Codeigniter Framework. The final results of this study will be a Geographic Information System form for training distribution by displaying training locations, training data, as well as video documentation when training takes place, the data will be presented in Google Maps form so that it can easily find the location of training deployments that can later be used as a reference to determine the next training location